Toponimi Kampung di Sepanjang Sungai Cimande Sebagai Basis Mitigasi Bencana Hidrologi - Aras, Taufik Setyadi; Suhanda, Dadi (Jayapangus Press, 2025)
Villages along the Cimande River are prone to hydrogeological disasters, such as floods and landslides, and have become increasingly densely populated with residential and industrial areas. Toponymic research in this area reveals local knowledge about river hydrology dynamics and can inform culture-based disaster mitigation strategies. This study examines the structure and meaning of village toponymy along the Cimande River, analyzes its correlation with hydrogeological disaster vulnerability, and formulates a mitigation model based on local wisdom. This study employs a qualitative approach with an anthropological focus, collecting data through in-depth interviews, observations, and documentation studies. Informants were purposely selected from among traditional leaders with knowledge of local history. The results show that village toponymy in this region contains many geographical and hydrological elements. For example, the word Leuwi